Climate change mitigation in Germany: rhetoric or reality? - Becker, Benjamin; Richter, Caspar (Momentum Quarterly, 2015)
Germany is widely considered particularly successful in climate change mitigation policy. A strong and growing economy coupled with twenty years of decreasing emissions are seen as proof that Germany has taken responsibility for its CO2 and has started on its way towards a low-carbon economy. Past policies like the promotion of energy efficiency and renewable energies, as well as future strategies like Germany’s energy transition (“Energiewende”) and participation in the EU Emission Trading System, are seen as having a recognizable impact on Germany’s CO2-emissions and helping the country to continue on its ambitious mitigation path. Consequently, it is commonly held that Germany can be an example for the climate policies of other countries. Taking a critical look at the past results and future strategies of Germany’s climate change mitigation policies, we arrive at a fundamentally different conclusion. We find that the past reductions in greenhouse gases have very little to do with purposeful legislation, that Germany’s contribution towards global CO2 emission has remained about the same since 1999, and that the net effect of the energy transition policies will be close to zero in the next decade as far as CO2 emissions are concerned. In this light, Germany’s image as a trailblazer in climate change mitigation appears to be mere rhetoric. We suggest that rhetoric is an unlikely path towards more climate- protection, and advocate a new, “carbon-factual” approach for assessing climate policy.
Keywords: Climate change mitigation; climate policy discourses; energy transition; energy efficiency; emissions trading